2022
DOI: 10.1111/febs.16331
|View full text |Cite
|
Sign up to set email alerts
|

FGF signalling facilitates cervical cancer progression

Abstract: Cervical cancer is one of the most frequently diagnosed cancers in women worldwide. While cervical cancer is caused by human papillomavirus (HPV), not all females infected with HPV develop the disease, suggesting that other factors might facilitate its progression. Growing evidence supports the involvement of the fibroblast growth factor receptor (FGFR) axis in several cancers, including gynecological. However, for cervical cancer, the molecular mechanisms that underpin the disease remain poorly understood, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 98 publications
1
12
0
Order By: Relevance
“…This work presented by Mahmood et al in The FEBS Journal [7] clearly indicated a crucial role for FGFR signaling in malignancy development during the progression of cervical cancer. The obtained data suggest, as in the case of other tumors, that small‐molecule FGFR inhibitors might be successfully used in targeted therapy against cervical cancer and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…This work presented by Mahmood et al in The FEBS Journal [7] clearly indicated a crucial role for FGFR signaling in malignancy development during the progression of cervical cancer. The obtained data suggest, as in the case of other tumors, that small‐molecule FGFR inhibitors might be successfully used in targeted therapy against cervical cancer and improve patient outcomes.…”
Section: Discussionmentioning
confidence: 94%
“…FGFR1 inhibitors are used in the treatment of various diseases. Zhang et al reported that the FGFR1 inhibitor PD173074 effectively inhibited p-FGFR1 phosphorylation and increased the threshold for mechanical pain in rats with myofascial pain syndrome (65). NSC12 is a small molecule inhibitor that could orally inhibit the interaction of FGF2/FGFR.…”
Section: Discussionmentioning
confidence: 99%
“…Also featured in this Subject Collection is a research article from Hiba‐Tun‐Noor Afshan Mahmood et al . [6] that investigates the role of fibroblast growth factor receptor (FGFR) signaling in cervical cancer. Fibroblast growth factor receptor regulates numerous biological processes during normal development and is hyperactivated in many cancers.…”
Section: Developmental Signaling Pathways In Disease Mechanismsmentioning
confidence: 99%